Social Representation of Japanese Characters in Zainichi Film - Santi Andayani; Emma Rahmawati Fatimah; Gathisa Silvia Gunawan; Aisyah Bellatrix Kancanadewi (Universitas Diponegoro, 2021)
Discriminative treatment and zainichi identity crisis have often focused on zainichi-themed literary and media works. In terminology, zainichi is a term for ethnic Koreans living in Japan. Koreans are victims because of their minority, and Japanese are portrayed as perpetrators who discriminate against them. This study focuses on the representation of Japanese people through the main characters in the film Zainichi, Hotaru (2001) and For Those We Love (2007), which are the objects of this research. This study uses the representation theory by Stuart Hall to propose how Japanese people are represented in the zainichi film media. This research uses documentation and literature study techniques for data collection and descriptive qualitative methods for data analysis The results showed that the representation of the Japanese through the main characters in the two films emphasized more the positive or humanist Japanese characters: 1) people who respect other nations; 2) people who are compassionate and appreciate human values; 3) people who are considerate; 4) trustworthy people; 5) people who are loyal and committed to their friends and lovers.